Checklist of sedentary Polychaete from Peru - Tarazona B., Juan (1974)
Taxonomical lists of different zoological groups have great value, since they constitute the basis for future zoogeographical and ecological studies. These lists are particularly important in countries of this part of the Pacific, where they are very rare. In Peru is recognized some list of mollusk and crustaceans, but none on polychaetes, which together with the aforementioned, are the most important groups of the marine ecosystem.